The development of the printing industry in Lithuania in 1918–1940 - Glosienė, Audronė (Knygotyra, 1992)
The article deals with history of printing houses in Lithuania in 1918–1940. The development of printing industry after the First World war and the activity of the main printing houses during the twenty years are shown. The State printing house was established in 1918 and continued its work until 1928 when it was joined with the printing company “Švyturys”. It was the begining of the largest and most powerful printing company “Spindulys”. Mighty printing companies were “Dirva”, “Žaibas”, “Varpas” and others. The great amount of the printing houses were small private ones. Many of them were not capable to print books or periodicals. In 1939 there were 101 printing houses in Lithuania. The article ends with the list of the printing houses.